2019
DOI: 10.3389/fmicb.2019.01926
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Regulon of the Bradyrhizobium diazoefficiens NnrR Transcription Factor: New Insights Into the Denitrification Pathway

Abstract: Denitrification in the soybean endosymbiont Bradyrhizobium diazoefficiens is controlled by a complex regulatory network composed of two hierarchical cascades, FixLJ-FixK 2 -NnrR and RegSR-NifA. In the former cascade, the CRP/FNR-type transcription factors FixK 2 and NnrR exert disparate control on expression of core denitrifying systems encoded by napEDABC , nirK , norCBQD ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 56 publications
(133 reference statements)
1
21
0
Order By: Relevance
“…Environmental cues (oxygen tensions and nitrogen oxides) and regulatory proteins (FixK 2 and NnrR) governing denitrification in B. diazoefficiens are well-known [19,20,25] (Figure 1). In this work, we have validated, under physiological conditions, the importance of the FixK 2 and NnrR transcription factors in real-time N 2 O dynamics using a robotized incubation system.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental cues (oxygen tensions and nitrogen oxides) and regulatory proteins (FixK 2 and NnrR) governing denitrification in B. diazoefficiens are well-known [19,20,25] (Figure 1). In this work, we have validated, under physiological conditions, the importance of the FixK 2 and NnrR transcription factors in real-time N 2 O dynamics using a robotized incubation system.…”
Section: Discussionmentioning
confidence: 99%
“…Our results from the denitrification analyses support other studies showing that complete denitrification pathways are more common in the B. japonicum supergroup than in other phylogenetic branches of Bradyrhizobium Although this suggests that some taxonomic groups of bradyrhizobia have higher frequency of complete denitrifiers than others, taxonomic position cannot be used as an indicator of the denitrification end-product since even very closely related strains may differ in this regard (Mania et al, 2020). Recent research has revealed several transcriptional and post-transcriptional mechanisms that influence the amounts of intermediate products released from denitrifying organisms (Liu et al, 2013;Torres et al, 2016;Lycus et al, 2018;Gaimster et al, 2019;Jiménez-Leiva et al, 2019). Although of value by itself, such information may be anecdotal.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed several transcriptional and post‐transcriptional mechanisms that influence the amounts of intermediate products released from denitrifying organisms (Liu et al ., 2013; Torres et al ., 2016; Lycus et al ., 2018; Gaimster et al ., 2019; Jiménez‐Leiva et al ., 2019). Although of value by itself, such information may be anecdotal.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed several transcriptional and post-transcriptional mechanisms that influence the amounts of intermediate products released from denitrifying organisms [56][57][58][59][60]. Although of value by itself, such information may be anecdotal.…”
Section: Discussionmentioning
confidence: 99%